If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 14 = -56 + -5x Reorder the terms: 14 + 5x = -56 + -5x Solving 14 + 5x = -56 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 14 + 5x + 5x = -56 + -5x + 5x Combine like terms: 5x + 5x = 10x 14 + 10x = -56 + -5x + 5x Combine like terms: -5x + 5x = 0 14 + 10x = -56 + 0 14 + 10x = -56 Add '-14' to each side of the equation. 14 + -14 + 10x = -56 + -14 Combine like terms: 14 + -14 = 0 0 + 10x = -56 + -14 10x = -56 + -14 Combine like terms: -56 + -14 = -70 10x = -70 Divide each side by '10'. x = -7 Simplifying x = -7
| x+31+61=5x-22 | | 1x/4=8(x-3) | | -3p-4+4p+8=x | | r+10=22 | | 2b-10=b | | 25x+15y=305 | | 9x+11x=180 | | B=2b-10 | | 5abcdefg=6abcdefg-2a+3b | | 10x^3+2y=0 | | 12x+2x=7 | | 0=64x^2-36 | | 2x+y=X | | 6x+9=4x-7 | | a(abc)= | | 63=x-27 | | 7x+16y=11 | | x+37=91 | | (3b-6)+(4b-6b+10)= | | p+(2p+15)+(p+15)=360 | | 16x^2+9=5 | | .15+.2m=.55 | | 1+4v+6v=-19 | | 6*[5*(3*3*3-17)]= | | 3w-9=36 | | 3(y+7)=4(y-7) | | (2y-1)(2y+4y-3)= | | x-6=89 | | 6In(3x)=8 | | -6x+6(5x+5)=-90 | | x=1.34*(x-90000) | | x=1.3*(x-90000) |